DKK1 and Its Receptors in Esophageal Adenocarcinoma: A Promising Molecular Target - Markos Despotidis; Orestis Lyros; Tatiana S. Driva; Panagiotis Sarantis; Emmanouil I. Kapetanakis; Adam Mylonakis; Andreas Mamilos; Stratigoula Sakellariou; Dimitrios Schizas (Diagnostics)
Esophageal adenocarcinoma (EAC) is an aggressive gastrointestinal (GI) malignancy with increasing incidence. Despite the recent progress in targeted therapies and surgical approaches, the survival rates of esophageal adenocarcinoma patients remain poor. The Dickkopf (DKK) proteins are secretory proteins known mainly as antagonists of the Wnt/β-catenin signaling pathway, which is considered an oncogene. However, it has been shown that in several GI cancers, including esophageal cancer, DKK1 may act as an oncogene itself through Wnt-independent signaling pathways. LRP5\6 and Kremen1/2 (Krm1/2) are transmembrane receptors to which the DKK proteins are mainly known to bind. CKAP4 (cytoskeleton-associated protein 4) is a novel receptor of DKK1, and the DKK1-CKAP4 pathway seems to be crucial in the role of DKK1 as an oncogene. The aim of this review is to feature the essential role of DKK1 and its receptors in carcinogenesis with a focus on EAC in an era of urgent need for specific biomarkers along with improved targeted therapies.